Scientific and philosophical theory of sports: real state and development prospects - Mamedov A.A.; Sherstyuk M.V.; Zaitsev A.A.; Gnezdilova E.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to based on critical analysis, substantiate the development of a philosophical theory of physical culture and sports. Methods and structure of the study. The arguments through which the evidentiary basis for the development of a philosophical theory of physical culture and sports are based are considered. The source base consists of scientific works devoted to the conceptual foundations of the development of philosophy and sports science. Results and conclusions. In the need to develop a scientific and philosophical theory of physical culture and sport, the authors present arguments that consist in resolving such problems as the different understanding in Russian and foreign science of the subject of the philosophy of sport itself, the interpretation of the phenomenon of sport, the historical and philosophical presentation of modern science of sport, three theoretical dimensions sports, historical and philosophical falsification, consideration of the philosophy of sport as the philosophy of Olympism and its historical and philosophical falsification, logical and linguistic inconsistency of the profile thesaurus. The authors conclude that, as a theoretical perspective, the design of a scientific and philosophical theory of sport is possible provided that all problematic issues considered in the study are systematically resolved. The structure of the model of scientific and philosophical theory presented in the article involves the development of a number of sections of philosophical applied knowledge in the fields of history, science, religion, politics, culture, and logical-linguistic analysis.